The impact of skills shortage on economic development in Germany – A mixed method approach - Tobias Johannes Hertrich; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2024)
In Europe, there is an increasing shortage of skilled workers and jobs remain vacant for long periods of time. The shortage of skilled workers has become a key issue for various stakeholders, as it not only makes it difficult to recruit and retain employees, but it is also seen as a significant barrier to innovation for companies. So far, most analyses of skills shortage take place at company level. We supplement this with a regional perspective, because many measures, especially those of policy makers, are conducted on the regional level. We examine the impact of skills shortage on various aspects of regional economic development. Using the spatial vector autoregressive panel model, significant effects on gross domestic product (GDP), employment are found, but not on research and development (R&D) activities. Expert interviews are used to dig deeper into the reasons for these findings, showing that the disadvantages of skills shortages on innovativeness are perceived, but relate to the future or to the more general economic situation. – – In Europa herrscht ein zunehmender Mangel an qualifizierten Arbeitskräften, und Stellen bleiben über lange Zeiträume unbesetzt. Der Fachkräftemangel ist für verschiedene Interessengruppen zu einem zentralen Thema geworden, da er nicht nur die Einstellung und Bindung von Mitarbeitern erschwert, sondern auch als erhebliches Innovationshemmnis für Unternehmen angesehen wird. Bislang wurden die meisten Analysen des Fachkräftemangels auf Unternehmensebene durchgeführt. Wir ergänzen dies um eine regionale Perspektive, da viele Maßnahmen, insbesondere die der politischen Entscheidungsträger, auf regionaler Ebene durchgeführt werden. Wir untersuchen die Auswirkungen des Fachkräftemangels auf verschiedene Aspekte der regionalen Wirtschaftsentwicklung. Unter Verwendung des räumlichen vektorautoregressiven Panelmodells werden signifikante Auswirkungen auf das Bruttoinlandsprodukt (BIP) und die Beschäftigung festgestellt, nicht jedoch auf die Forschungs- und Entwicklungsaktivitäten (FuE). Experteninterviews werden genutzt, um die Gründe für diese Ergebnisse zu ergründen, und zeigen, dass die Nachteile des Fachkräftemangels für die Innovationsfähigkeit zwar wahrgenommen werden, sich aber auf die Zukunft oder die allgemeine Wirtschaftslage beziehen.
Keywords: O10; O30; J23; J21; J11; 330; skills shortage; regional development; regional innovativeness; mixed methods